Preparation of AgI/Silica/Poly(Ethylene Glycol) Nanoparticle Colloid Solution and X-Ray Imaging Using It. (30th July 2013) - Kobayashi, Yoshio; Ayame, Tetsuya; Nakagawa, Tomohiko; Kubota, Yohsuke; Gonda, Kohsuke; Ohuchi, Noriaki
Abstract : This work performed X-ray imaging of mouse by using aqueous colloid solution of AgI nanoparticles coated with silica (AgI/SiO2 ) and then surface-modified with poly(ethylene glycol) (PEG) (AgI/SiO2 /PEG). A colloid solution of AgI nanoparticles was prepared by mixing silver perchlorate and potassium iodide in water. The AgI nanoparticles were surface-modified with 3-mercaptopropyltrimethoxysilane and then were silica-coated by a sol-gel reaction between tetraethylorthosilicate and H2 O catalyzed with NaOH in ethanol. The AgI/SiO2 particle surface was modified with PEG by using methoxy PEG silane CH 3 O CH 2 CH 2 O n CH 2 CONH C 3 H 6 Si O C 2 H 5 3 . The AgI/SiO2 /PEG colloid solution revealed a computed tomography value as high as 1343.6 HU at an iodine concentration of 0.1 M, which was higher than a commercial X-ray contrast agent with the same iodine concentration. Tissues of mouse could be imaged by injecting the concentrated colloid solution into them.